2015
DOI: 10.1002/mds.26251
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the nigrostriatal fibers in Parkinson's disease

Abstract: Background Parkinson’s disease (PD) is histopathologically characterized by the loss of dopamine neurons in the substantia nigra pars compacta. The depletion of these neurons is thought to reduce the dopaminergic function of the nigrostriatal pathway, as well as the neural fibers that link the substantia nigra to the striatum (putamen and caudate), causing a dysregulation in striatal activity that ultimately leads to lack of movement control. Based on diffusion tensor imaging, visualizing this pathway and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 45 publications
14
100
2
1
Order By: Relevance
“…The first 3 brain regions exactly matched 3 of the 4 areas that we identified in our study. Moreover, recent tractography studies in de novo PD patients with the putamen as seed region and the SN as target region revealed reduced mean putamen–SN connectivity as a surrogate marker for a decline of the nigrostriatal system . Intriguingly, Zhang and colleagues used datasets of 50 de novo PD patients and 27 healthy controls from the PPMI cohort, as we did.…”
Section: Discussionmentioning
confidence: 82%
“…The first 3 brain regions exactly matched 3 of the 4 areas that we identified in our study. Moreover, recent tractography studies in de novo PD patients with the putamen as seed region and the SN as target region revealed reduced mean putamen–SN connectivity as a surrogate marker for a decline of the nigrostriatal system . Intriguingly, Zhang and colleagues used datasets of 50 de novo PD patients and 27 healthy controls from the PPMI cohort, as we did.…”
Section: Discussionmentioning
confidence: 82%
“…3). Several anatomical MRI studies using diffusor tensor imaging reported PD-related reduction of structural connectivity between substantia nigra and striatum (Du et al, 2011, Hacker et al, 2012, Nilsson et al, 2007, Péran et al, 2010, Yoshikawa et al, 2004, Zhan et al, 2012, Y. Zhang et al, 2015, J.…”
Section: Discussionmentioning
confidence: 99%
“…As well as considering the striatal and the SN region separately, attempts to investigate alterations in the nigrostrital pathway exist . Because of the small size of the SN and the close proximity to extrapyramidal tracts, it is difficult to delineate the nigrostrital tract from common imaging protocols in humans.…”
Section: Discussionmentioning
confidence: 99%